Low level of the dental health as an indicator of malignant of the oral mucosa - E. V. Kochurova; V. N. Nikolenko; E. O. Kudasova; O. I. Panferova; O. S. Guiter; A. V. Sepp; A. V. Zotov (Опухоли головы и шеи, 2024)
Introduction. The manifestation of oncological alertness during dispensary observation by a dentist is very important. The most accessible options for preventing malignancy of the oral mucosa are sanitation, regular professional oral hygiene, as well as educational work among doctors and the population. However, despite the visual accessibility of tissues and organs of the oral cavity, there is an annual increase in malignant neoplasms in this area. In this case, most patients are diagnosed with a tumor process of the last stage. malignant neoplasms of the head and neck organs require special attention due to high risk of disability even at an early stage.   Aim. To evaluate a correlation between malignancy of the oral mucosa and the burdened dental status of patients.   Materials and methods. A controlled study was conducted which included 142 patients with cancer of the oral mucosa without sequential or parallel inclusion of patients in groups. Dental status was assessed at help-seeking stage or during clinical examination, as planned, by evaluation of main dental indices. The morphological diagnosis was established using histological verification.   Results. The majority of patients with oral tumors had hard dental plaque (81.7 % of cases). The condition of the soft tissues, in addition to presence of the mucous membrane lesion, was characterized by bleeding (69 % of cases). moderate periodontal pathology was detected (19 % of cases). patients with the cavity tumors had an acute traumatic edge of hard tissues (70 % of cases), extensive caries (26 % of cases) and the presence of removable dentures (82 % of cases).   Conclusion. The values of parameters evaluated in patients in the study with squamous cell carcinoma of the oral mucosa show its relation to aggravation of general somatic status. All patients in the study required dental treatment and training in oral hygiene care.